2011
DOI: 10.3945/ajcn.110.002212
|View full text |Cite
|
Sign up to set email alerts
|

Baseline leptin and leptin reduction predict improvements in metabolic variables and long-term fat loss in obese children and adolescents: a prospective study of an inpatient weight-loss program

Abstract: Background: It is unclear whether high plasma leptin in obese individuals represents leptin resistance or whether individuals with marked reductions in leptin concentrations in response to weight loss may be at greater risk of regaining weight. Moreover, whether changes in leptin predict metabolic improvements during weight loss is uncertain. Objective: The objective was to prospectively examine associations between plasma leptin, body fat, and weight and metabolic risk factors in obese children during weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
59
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 40 publications
3
59
1
1
Order By: Relevance
“…This particular finding is important because leptin is an independent predictor of increasing BMI, 21,22 and is associated with reduced weight loss efficacy, in youth. 26,27 Our finding of exceedingly high levels of leptin in EO children is congruent with a previous report by Freedman et al 5 demonstrating very strong tracking of adiposity from childhood to adulthood in EO youth. Therefore, in addition to the immediate metabolic and vascular consequences of hyperleptinemia in extreme pediatric obesity, the exceedingly high leptin levels in this group portend an increased risk of weight gain over time and potentially reduced efficacy of weight loss interventions in this subset of obese youth and suggest that standard approaches to weight management may be less effective in these children.…”
Section: Discussionsupporting
confidence: 82%
“…This particular finding is important because leptin is an independent predictor of increasing BMI, 21,22 and is associated with reduced weight loss efficacy, in youth. 26,27 Our finding of exceedingly high levels of leptin in EO children is congruent with a previous report by Freedman et al 5 demonstrating very strong tracking of adiposity from childhood to adulthood in EO youth. Therefore, in addition to the immediate metabolic and vascular consequences of hyperleptinemia in extreme pediatric obesity, the exceedingly high leptin levels in this group portend an increased risk of weight gain over time and potentially reduced efficacy of weight loss interventions in this subset of obese youth and suggest that standard approaches to weight management may be less effective in these children.…”
Section: Discussionsupporting
confidence: 82%
“…Likely, Murer et al [50] did show that changes in leptin levels were predictors for cholesterol and LDL-cholesterol after a WL program in obese children and adolescents [50]. Our results indicate that the greater the reduction in CT-1 levels, the greater the reduction in cholesterol levels, confirming the potential role of CT-1 in ameliorating unfavorable metabolic features.…”
Section: Discussionsupporting
confidence: 81%
“…Evidence from clinical studies showed that 5% reduction in body fat percentage improved cardiometabolic risk profile in obese children (21) and adults (22). Very few experimental studies have focused on prevention of obesity and metabolic Few studies have shown that exposure to n3 long-chain polyunsaturated fatty acids throughout life protects against the detrimental effects of an adverse fetal environment on blood pressure, inflammation, leptin sensitivity, and glucose homeostasis in adult rats (26,27).…”
Section: Discussionmentioning
confidence: 99%